Advancing the relationship between renewable energy and ecosystem services for landscape planning and design: A literature review - Picchi, Paolo; van Lierop, Martina; Geneletti, Davide; Stremke, Sven (Ecosystem services, 2019)
•Few papers on renewable energy explicitly apply the ecosystem services framework.•The most considered were the cultural ecosystem services groups.•The “integrated planning approach” can safeguard the supply of ecosystem services.•Diversified spatial reference systems per ecosystem services are needed.•Participatory processes are needed for cultural ecosystem services groups. The transition to a low carbon future is starting to affect landscapes around the world. In order for this landscape transformation to be sustainable, renewable energy technologies should not cause critical trade-offs between the provision of energy and that of other ecosystem services such as food production. This literature review advances the body of knowledge on sustainable energy transition with special focus on ecosystem services-based approaches and methods. Two key issues emerge from this review: only one sixth of the published applications on the relation between renewable energy and landscape make use of the ecosystem service framework. Secondly, the applications that do address ecosystem services for landscape planning and design lack efficient methods and spatial reference systems that accommodate both cultural and regulating ecosystem services. Future research efforts should be directed to further advancing the spatial reference systems, the use of participatory mapping and landscape visualizations tools for cultural ecosystem services and the elaboration of landscape design principles.